Squamoid Eccrine Ductal Carcinoma: A Diagnostic - Sharma, Bhavna; Malhotra, Purnima; Bhardwaj, Minakshi (Annals of Pathology and Laboratory Medicine, 2018)
Eccrine carcinomas comprise less than 0.01% of all cutaneous malignancies. Squamoid eccrine ductal carcinoma is an exceedingly rare variant that exhibits both squamous and eccrine ductal characteristics. It presents in patients older than 50 years on the head, neck, and trunkas nodule or plaque. It is commonly misdiagnosed as squamous cell carcinoma from which it must be differentiated as its recurrence and metastasis rates are much higher.Very few cases have been reported, we hereby report an additional case of this rare tumor. A 50 years old male presented with a slow-growing nodule in the frontal region of scalp since one year. Histopathology showed a dermal based infiltrativeepithelial tumor with extensive squamous differentiation arranged in interlacing cords and nests, with focal formation of ductal lumina which was highlighted by immunohistochemistry. The diagnostic identification of eccrine carcinomas is hampered by their rarity .Awareness of this rare entity will help in accurate diagnosis and management.